2010
DOI: 10.1121/1.3372756
|View full text |Cite
|
Sign up to set email alerts
|

Click- and chirp-evoked human compound action potentials

Abstract: In the experiments reported here, the amplitude and the latency of human compound action potentials ͑CAPs͒ evoked from a chirp stimulus are compared to those evoked from a traditional click stimulus. The chirp stimulus was created with a frequency sweep to compensate for basilar membrane traveling wave delay using the O-Chirp equations from Fobel and Dau ͓͑2004͒. J. Acoust. Soc. Am. 116, 2213-2222͔ derived from otoacoustic emission data. Human cochlear traveling wave delay estimates were obtained from derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 17 publications
4
46
0
1
Order By: Relevance
“…Further, the interval between wave-I and wave-V peaks has been shown to be remarkably robust across stimulus level in ABR recordings (Don and Eggermont, 1978;Eggermont and Don, 1980), indicating that a level-dependent UR is not required. Contradictory to this, however, Chertoff et al (2010) measured CAPs latency in humans, and demonstrated that CAPs could have a smaller latency change with level than what has been reported for ABR wave-V latency (Serpanos et al, 1997;Dau, 2003;. This would tend to suggest that the wave-I (which is believed to have the same origin as the CAP) to wave-V interval, and thus the UR, should be level-dependent.…”
Section: B Effects Of the Ur Functionmentioning
confidence: 87%
See 1 more Smart Citation
“…Further, the interval between wave-I and wave-V peaks has been shown to be remarkably robust across stimulus level in ABR recordings (Don and Eggermont, 1978;Eggermont and Don, 1980), indicating that a level-dependent UR is not required. Contradictory to this, however, Chertoff et al (2010) measured CAPs latency in humans, and demonstrated that CAPs could have a smaller latency change with level than what has been reported for ABR wave-V latency (Serpanos et al, 1997;Dau, 2003;. This would tend to suggest that the wave-I (which is believed to have the same origin as the CAP) to wave-V interval, and thus the UR, should be level-dependent.…”
Section: B Effects Of the Ur Functionmentioning
confidence: 87%
“…Further, the CAP latencies of Chertoff et al (2010) decrease by À0.030 ms/ dB over the level range of 75-105 dB SPL. So, even if a level-dependent UR was implemented to account for the difference in latency change between Chertoff et al (2010) and , the AN model would still underpredict the wave-V latency. It thus remains unclear why the model fails to account more accurately for the leveldependent behavior of wave-V latency.…”
Section: Wave-v Latency Dependency On Frequency and Levelmentioning
confidence: 97%
“…CAP measurements were made from the first negative peak in the ABR waveform recorded with an electrode placed on the tympanic membrane (Lichtenhan & Chertoff 2008; Chertoff et al 2010). The MOC reflex was activated by contralateral acoustic stimulation (CAS) that was alternated on and off across runs.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, wave V latency decreases with increasing frequency (e.g., Gorga et al, 1988;Dau, 2003;Rasetshwane et al, 2013), reflecting the shorter travel time required by the traveling wave to excite more basal (higher-frequency) regions of the cochlea. Additionally, when evoked by rising-frequency chirps designed to compensate for traveling-wave dispersion, the amplitude of wave V is larger than it is for both clicks and falling-frequency chirps (Dau et al, 2000;Elberling and Don, 2008; wave I amplitude exhibits similar behavior- Shore and Nuttall, 1985;Chertoff et al, 2010).…”
Section: Introductionmentioning
confidence: 92%